Elegant Science - Arturo Casadevall (American Society for Microbiology, 2018)
ABSTRACT Elegance is a prized quality in science that is associated with simplicity and explanatory power. This essay considers the qualities that make a scientific model, experiment, method, or theory “elegant,” with a focus on the life sciences. We propose a definition of elegance that includes clarity, cleverness, correctness, explanatory power, parsimony, and beauty. The pursuit of elegance can improve the quality of science, but elegance must be pursued with caution, as the truth is sometimes inelegant.